Discovering statistics using SPSS : (and sex and drugs and rock 'n' roll). - Field, Andy P., 1973- (London : SAGE, 2011)
Written in his vivid and entertaining style, Andy Field provides students with everything they need to understand, use and report statistics-at every level-in the Third Edition of Discovering Statistics Using SPSS. Retaining the strong pedagogy from previous editions, he makes statistics meaningful by including playful examples from everyday student life (among other places), creating a gateway into the often intimidating world of statistics. In the process, he presents an opportunity for students to ground their knowledge of statistics through the use of SPSS.
Keywords: SPSS